The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1088/0957-4484/16/11/023
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of plasmon resonances during plasma deposition of silver nanoparticles

Abstract: In situ real-time spectroscopic ellipsometry is used to monitor the growth of magnetron sputtered silver nanoparticles on SiO 2 substrates, through the percolation threshold and into the bulk film regime. The plasmon polariton resonances in the nanoparticulate regime are effectively modelled by a Lorentz oscillator. The resonance energy of the oscillator is observed to reduce to zero shortly after the percolation threshold, whereby the oscillation is described by Drude free electron theory. From the Drude theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 22 publications
7
97
0
1
Order By: Relevance
“…An exception with respect to the trends described above is the 1 nm AlOxNy sample, the transmission spectrum of which also exhibits a wide absorption feature (i.e., significantly lower transmission with respect to the other samples) extending from ~1 to ~2 eV, while the primary resonance position is located at ~2.61 eV as compared to ~2.43 eV for the 2 nm AlOxNy sample. The appearance of a second plasmonic resonance frequency (as in the case of the 1 nm AlOxNy sample in the present study) has been reported in the literature, for metal thin films close to the percolation threshold, and has been attributed to exceptionally strong dipole interaction triggered by the close proximity of metal atomic islands 56 . However, changes in the particles shape and size as the AlOxNy layer becomes thinner and does not fully cover Ag, may also explain the observed trends in the optical properties in accordance with earlier reported data on model plasmonic systems 2 .…”
Section: Resultssupporting
confidence: 84%
“…An exception with respect to the trends described above is the 1 nm AlOxNy sample, the transmission spectrum of which also exhibits a wide absorption feature (i.e., significantly lower transmission with respect to the other samples) extending from ~1 to ~2 eV, while the primary resonance position is located at ~2.61 eV as compared to ~2.43 eV for the 2 nm AlOxNy sample. The appearance of a second plasmonic resonance frequency (as in the case of the 1 nm AlOxNy sample in the present study) has been reported in the literature, for metal thin films close to the percolation threshold, and has been attributed to exceptionally strong dipole interaction triggered by the close proximity of metal atomic islands 56 . However, changes in the particles shape and size as the AlOxNy layer becomes thinner and does not fully cover Ag, may also explain the observed trends in the optical properties in accordance with earlier reported data on model plasmonic systems 2 .…”
Section: Resultssupporting
confidence: 84%
“…20,[24][25][26]29,30,46 The samples were subsequently measured more extensively ex situ with a J. A. Woollam Co., Inc. VASE system to collect angle-and energy-resolved VAMM and scattering spectra.…”
Section: Acs Photonicsmentioning
confidence: 99%
“…Common causes of depolarization include surface roughness, film thickness inhomogeneity, backside reflection from a weakly absorbing substrate, and plasmon resonance of nanostructures. 17,25 Note that the feature cannot be explained by enhanced coupling to the out-of-plane mode; otherwise, the feature would have grown stronger as θ i increased. Instead, the feature vanishes at larger θ i due to the shadowing effects of the larger NPs and the increasing contribution of their out-of-plane LSPR mode whose maximum occurs at 4.75 eV.…”
Section: ■ Depolarizing Behavior Of Nanoparticles With a Bimodal Sizementioning
confidence: 99%
“…This is in accordance with the observed growth behaviour of ultrathin Ag films deposited from the plasma phase on oxide layers. 33,34 Below the percolation threshold, a predominantly island growth mechanism occurs whilst a layer-by-layer growth predominates after percolation. 32,33 Therefore, we identified this point with the percolation threshold of the Ag cluster layer.…”
mentioning
confidence: 99%
“…At the percolation threshold, the optical properties of the film changes drastically, and the maximum surface plasmon resonance takes place. 33,37 Fig . 3(c) shows the integrated intensity of the aforementioned SERS bands at different thiophenol concentrations for the substrate with an effective thickness of 5.6 6 0.1 nm.…”
mentioning
confidence: 99%